The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s11136-006-0040-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing translations of the EORTC QLQ-C30 using differential item functioning analyses

Abstract: The European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30 is one of the most widely used quality of life instruments for cancer patients. The aim of this study was to assess whether there were linguistic differences in the way an international sample answered the EORTC QLQ-C30 questionnaire. Thirteen translations of the EORTC QLQ-C30, representing 22 countries, were investigated using a database of 27,891 respondents, incorporating 103 separate studies. Differential item functioning (DIF) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
158
3
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(189 citation statements)
references
References 25 publications
21
158
3
7
Order By: Relevance
“…The statistical methodology was identical to that used in the previous papers examining the EORTC QLQ-C30 at baseline [6,7]. Differential item functioning (DIF) analyses using ordinal logistic regression using Stata 10 software were used to investigate whether responses to a particular item differed from other items in the same scale with respect to the translation used after controlling for the overall scale score and adjusting for other variables.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical methodology was identical to that used in the previous papers examining the EORTC QLQ-C30 at baseline [6,7]. Differential item functioning (DIF) analyses using ordinal logistic regression using Stata 10 software were used to investigate whether responses to a particular item differed from other items in the same scale with respect to the translation used after controlling for the overall scale score and adjusting for other variables.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…We previously reported two sets of DIF analyses of a large database of questionnaire responses to the European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30, a cancer-specific QoL instrument, and examined the evidence for different response patterns by both language of administration [6] and by cultural/geographic grouping [7]. The results suggested that most questionnaire items were answered similarly, regardless of the nationality of the respondent or the translation of the questionnaire used.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to note that sociodemographic and clinical variables asymmetries may markedly influence HRQoL and response patterns among different populations. 19,20 Such effects may influence decision-making, as the same intervention may have disparate effects among patients of different cultural backgrounds. This insight at least partly explains and justifies the importance of performing the translation of QLQ-OES18 and QLQ-OG25 to the national native language (in this case, Portuguese).…”
Section: Discussionmentioning
confidence: 99%
“…No existe correla- (44) ** No se ha encontrado ninguna investigación en español que aporte datos comparables con nuestra muestra, la única disponible es la de Arrarás, Martínez,Manterola, Salgado, Martínez, Vera, Illarramendi (2005) (45) cuya muestra está compuesta por 97 pacientes con NSCLC pero en estadios muy avanzados (III y IV). *** No se encontraron datos referenciales para los síntomas específicos de cáncer de pulmón medidos con el QLQ-LC13 **** Disnea-C30 hace referencia al síntoma de disnea medido por el cuestionario QLQ-C30 y Disnea-LC13 hace referencia al medido por el QLQ-LC13 ción negativa entre depresión y las escalas sintomáticas.…”
Section: Estado Emocionalunclassified